Jeszcze raz o tzw. mieczu św. Piotra z archikatedry poznańskiej - Głosek, Marian (Ecclesia. Studia z Dziejów Wielkopolski, 2011)
The author tackles the problem of determining the age of the so called „Sword of St. Peter”, its origin and possible circumstances of its appearance on the territory of the Piast state. He also makes an attempt to systematize in an orderly fashion the nomenclature of the sword using an analogy between the Poznañ relic and similar objects which have been discovered on the territory of 13th century Europe. Iconographic sources relating to weapons resembling the Poznañ sword include among others the scene of the „Arrest of Jesus in the Garden of Olives” from a panel of the Marian Altar of Wit Stwosz in Kraków.